Исследование особенностей рабочего процесса камеры сгорания ГТД мощностью 2,5 МВт, работающей на синтез-газе - Сербин, С. И.; Гончарова, Н. А.; Вилкул, В. В. (НТУ "ХПИ", 2015)
Статья посвящена вопросам численного моделирования рабочих процессов камер сгорания газотурбинных двигателей, работающих на синтез-газе. Авторами исследованы вопросы возможности применения синтез-газов в качестве основного топлива для камер сгорания. Рассмотрены вопросы применения конструктивных модификаций топливосжигающих устройств с целью применения RQL-технологии для улучшения экологических характеристик существующих камер сгорания газотурбинных двигателей.

This scientific paper is devoted to the issues of numerical simulation of working processes in the combustion chambers of synthetic gas–driven gas turbine engines. An ideal organization of the burning process in the combustion chamber is the main factor determining the ecological characteristics of the gas-turbine unit that together with technical and economic indices of the plant define its competitiveness. The three-dimensional investigation carried out to determine the influence of the synthetic gas composition on the working process in the combustion chamber of a diffusion type of the gas turbine engine of 2.5 MW showed that the replacement of the natural gas (methane) by the synthetic gas for the pilot combustion chamber of the gas turbine engine making no essential engineering changes of the flame tube results in an increased exhaust of toxic components, in particular nitrogen oxides NO in the range of 66 to 200 ppm depending on the fuel gas composition. It has been shown that an improvement in the performances of gas turbine engines and an increase in the stability of combustion processes of low-cal synthetic gases are possible due to the use of the double-zone technology proposed for the burning of hydrocarbon RQL fuels (Rich-Burn, Quick-Mix, Lean-Burn). It has been established that in order to decrease the emission of nitrogen oxides to 70 % for GTE when the combustion chamber is operated using the RQL technology in comparison with the traditional diffusion circuit it is necessary to create conditions for the efficient mixing of the reagents in the primary zone of the chamber preventing the formation of the mixture of a stochiometric composition in it, which is achieved through the choice of the rational relationships of the geometric sizes of the fuel burning plant, and the ratio of the diameter of the output section of the zone rich in fuel-&-air mixture to the diameter of the hot tube must be in the range of 0.40 to 0.55.
Studying the peculiarities of the working process in the combustion chamber of synthetic gas-operated turbine engine of 2.5MW
Keywords: газотурбинные установки; RQL-технология; высокозольные угли; математическое моделирование; combustion chamber; synthetic gas; RQL-technology; mathematic simulation; burning